Analysis of Carbon Tax Potential in Coal-Fired Power Plants (PLTU) of PT. Indonesia Power: A Comparison Between Carbon Tax Payments and Carbon Credit Purchases - Sueb, Memed; Devano, Sony; Tanzil , Nanny DewiTanzil; Soenaria, Syaiful Rahman; Affardi, Chirmala Wisnu Permata (Dinasti International Journal of Economics, Finance & Accounting, 2025)
Indonesia is ranked as the 9th largest CO2 emitter globally, with emissions reaching 192.7 million metric tons of carbon (mtC). The largest source of CO2 emissions in Indonesia comes from coal processing. Despite global efforts, Indonesia remains heavily reliant on coal to meet its electricity needs. This study aims to calculate the carbon emissions generated by coal-fired power plants (PLTUs), estimate the potential carbon tax implementation from 2021 to 2023, and analyze the optimal choice between paying carbon taxes or purchasing carbon credits as an alternative to mitigate environmental impacts. The research was conducted at PT. Indonesia Power's PLTU for the period of 2022-2024 using a descriptive analysis method with a qualitative approach. The results indicate that carbon emissions at PT. Indonesia Power's PLTU increased gradually from 2021 to 2023 due to delays in implementing the carbon tax, which encouraged continued reliance on environmentally unfriendly coal as the primary fuel source. The total potential carbon tax calculation for 2021-2023, based on Law No. 7 of 2021, amounts to IDR 4,437,619,050,000. This potential tax has shown a gradual increase in line with rising carbon emissions at the PLTU. The choice between paying carbon taxes and purchasing carbon credits depends on the long-term goals and financial condition of the PLTU. If the PLTU focuses on sustainable emission reductions, investing in environmentally friendly technologies is a more strategic option to avoid escalating carbon tax costs. However, if short-term financial flexibility is prioritized, purchasing carbon credits can serve as a practical solution for the PLTU.